(untitled) (The International Journal of Educational Sciences and Arts, 2025)
This research aims to uncover the profound and organic relationship between potential syntactic variations in the text of the Prophetic Hadith and the rhetorical exegesis (al-Tafsīr al-Bayānī) of the Holy Quran. The variation in the grammatical analysis of a single prophetic word is not a mere syntactic luxury but a hermeneutic key that leads to divergent understandings of the Quranic text’s semantics, its legal rulings, and its rhetorical secrets. Employing a descriptive-analytical methodology, the study examines selected applied models, most notably the hadith "The slaughter of the fetus is the slaughter of its mother" (Dhakātu al-janīni dhakātu ummihi), demonstrating how the variation between the nominative and accusative cases has directed exegetes and jurists in their interpretation of the general prohibition of carrion (al-maytah) in the Quran. The research concludes that precise grammatical analysis of the Prophetic Hadith is not merely an auxiliary science but a fundamental component of rhetorical exegesis and an indispensable tool for delving into the multiple layers of meaning within the Quranic text, emphasizing the necessity of methodological integration between the Arabic linguistic sciences and the Islamic sciences.